Structure effects on reaction mechanisms in collisions induced by halo and weakly bound nuclei around the Coulomb barrier - P. Figuera; V. Scuderi (Ядерна фізика та енергетика)
The study of reaction mechanisms in collisions induced by halo and/or weakly bound nuclei around the Coulomb barrier has recently been the subject of many theoretical and experimental papers. Here we discuss our present understanding of some aspects of such a topic by briefly summarizing experimental data obtained by different authors with particular attention to some results obtained in the last years by our collaboration.